Оцінка ефективності рішень VPN з відкритим вихідним кодом - Свiтличний, Є. Ю.; Агеєв, Д. В. (My University, 2025)
Virtual Private Networks (VPNs) are essential for ensuring secure connections between remote users and corporate networks. This study evaluates the performance of various Linux-based VPN solutions, comparing them in terms of overhead, bandwidth, latency, and security. Experimental results indicate that UDP-based VPNs offer higher efficiency and lower latency compared to TCP based alternatives.
Keywords: VPN з відкритим вихідним кодом; Virtual Private Network